2011
DOI: 10.1007/s11136-011-0051-0
|View full text |Cite
|
Sign up to set email alerts
|

The longitudinal association between glycaemic control and health-related quality of life following insulin therapy optimisation in type 2 diabetes patients. A prospective observational study in secondary care

Abstract: PurposeTo test whether improvement in glycosylated haemoglobin (HbA1c) as a marker of glycaemic control, following intensifying insulin therapy, is associated with improvements in HRQoL.MethodsDutch sub-optimally controlled (HbA1c > 7%) type 2 diabetes patients (N = 447, mean age 59 ± 11) initiated insulin glargine therapy. Data were collected at baseline, 3 and 6 months, and included HbA1c and measures of HRQoL: diabetes symptom distress (Diabetes Symptom Checklist-revised; DSC-r), fear of hypoglycaemia (Hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
18
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 27 publications
5
18
1
1
Order By: Relevance
“…Some studies found that a better glycemic control was associated with a better HRQoL, and that complications were the most important disease-specific determinant of HRQoL [15,16], whereas other authors found no significant relationship between the HRQoL and glycemic control [17,18]. In the present study, the effect of poor blood glucose control was not seen to be associated with any of the domains, and diabetes duration had no impact on the HRQoL.…”
Section: Discussioncontrasting
confidence: 72%
“…Some studies found that a better glycemic control was associated with a better HRQoL, and that complications were the most important disease-specific determinant of HRQoL [15,16], whereas other authors found no significant relationship between the HRQoL and glycemic control [17,18]. In the present study, the effect of poor blood glucose control was not seen to be associated with any of the domains, and diabetes duration had no impact on the HRQoL.…”
Section: Discussioncontrasting
confidence: 72%
“…As stated by Polonsky, the relationship between HRQoL and diabetes is bidirectional; aspects of diabetes may negatively impact on HRQoL, and impaired HRQoL may also negatively influence diabetes self-management and thus health outcomes (20). Therefore, it is relevant to explore and understand those factors implicated in this relationship to Some studies found that better glycemic control was associated with better HRQoL and that complications were the most important disease-specific determinant of HRQoL (4,21,22). However, other authors found no significant relationship between HRQoL and glycemic control (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Patients were invited to participate in the SPIRIT and ESPRIT studies by their primary or secondary care treating physician if there was a clinical necessity to initiate long-acting insulin. Both studies are described in more detail elsewhere (14,15). The present analyses used only baseline data collected before insulin initiation or intensification.…”
Section: Methodsmentioning
confidence: 99%